Analysis of Tax Compliance Challenges in Indonesia: Perspectives of Digitalization, Regulation, and Tax Literacy - Sri Hutami Adiningsih S; Ratnah S; Is Arianto Pratama; Kurniawan Kurniawan (Universitas Ichsan Sidenreng Rappang, 2026)
This study analyzes various challenges affecting tax compliance improvement in Indonesia through a literature review using a descriptive qualitative approach. Findings indicate that low tax literacy, regulatory complexity, barriers to digitalization, high compliance costs, and low public trust are the main factors hindering taxpayer compliance. Meanwhile, digitalization such as e-filing and e-billing have facilitated tax administration, but are not yet optimal due to digital literacy constraints. Efforts to improve compliance require ongoing education, regulatory simplification, improved public services, and increased government transparency.